Heart failure in the elderly - de Freitas, Elizabete Viana (Science Press, 2012)
The aging of the population is, currently, a major phenomenon, drawing the attention of a number of investigators. The significant increase of life expectancies over the past few decades, in addition to social and economic consequences, has lead to a major change in the morbidity and mortality profile of elders. Heart failure (HF) is a condition in which the heart can not pump enough blood to meet the body's needs. HF is predominantly a disorder of the elderly with rates increasing exponentially. The prevalence of HF approximately doubles with each decade of life. As people live longer, the occurrence of HF rises, as well as other conditions that complicate its treatment. Impaired heart function implies a reduced duration of survival. Fortunately, many factors that can prevent HF and improve outcome are known and can be applied at any stage. This review emphasizes the importance of factors inherent in aging itself, focusing on heart disease, particularly as a disease of aging, can help critically refine management of this acute and chronic disease, as well as foster preventive strategies to reduce the incidence of this common malady.